Population growth and status of the Nushagak Peninsula caribou herd in southwest Alaska following reintroduction, 1988 - 1993 - Hinkes, Michael T.; Van Daele, Lawrence J. (Rangifer, 1996)
Caribou were reintroduced to the Nushagak Peninsula, Alaska in February 1988, after an absence of over 100 years. The purpose was to reestablish caribou in the area and once again provide hunting to local residents. The Nushagak Peninsula caribou herd (NPCH) has grown rapidly from 146 reintroduced caribou to over 1000 in 6 years at an exponential rate of increase of r = 0.317 or about 38%. The dramatic growth of the herd was attributed to the initial high percentage of females in the herd, high calf production and survival, pristine range, few predators and no hunting. Abundant high quality forage on the Nushagak Peninsula is the probable reason for the enhanced body condition and high natality even among 2-year-olds, and it has most likely contributed to the high calf survival and recruitment. Lack of predators and hunting has allowed calf and adult mortality to remain low. Although the size of the NPCH has grown steadily over the past 6 years, no significant dispersal from the peninsula has occurred. The population density of the NPCH was estimated to be 1.0/km2 in 1993. We believe the herd will continue to grow, and could reach a density of 2.3/km2 by 1998, even with a 10% harvest beginning in 1995. While the current growth of the NPCH makes the réintroduction a success, the increasing density, lack of dispersal and potential for over-grazing, presents managers with hard decisions.